The Role of the Egyptian Working Class in Mubarak’s Ouster - Del Panta, Gianni (PARTECIPAZIONE E CONFLITTO, 2016)
The downfall of Hosni Mubarak’s regime in Egypt has often been portrayed as a ‘pure event’ - that is, something restricted to a couple of weeks in a single and specific square. This article seeks to direct-ly challenge this standard narrative, which has focused simply on what happened in Tahrir, arguing instead that Mubarak’s ouster from power was the result of longstanding anti-regime struggles that developed throughout the 2000s. In the implicit formation of that cross-class and cross-ideological coalition that even-tually defeated the regime, a crucial role was played by workers’ mobilizing against neoliberal policies. There are three main reasons for this: a) since the late 1990s workers were the most serious challenge to Mubarak’s regime; b) during the now famous eighteen days of relentless protests, workers were at the fore-front in the Nile Delta centers, as well as an important element in Tahrir; and finally c) when public enter-prises were re-opened on February 6, an unprecedented wave of strikes paralyzed the country, forcing the military to oust Hosni Mubarak in order to deflect the growing social soul of the uprising